Cupping Therapy Benefit in Glucose Blood Level - Rara Inggarsih (HM Publisher, 2021)
Some Muslims have used cupping therapy and occupies a popular position among other alternative therapeutic methods. Modern medical research evidence also confirms the benefits of the therapy recommended by the Prophet. Many medical experts know the efficacy of cupping therapy in treating disease. According to the International Diabetes Federation (IDF), in 2013, Indonesia was ranked seventh with diabetes. Cupping therapy plays a role in stimulating blood circulation in the muscles, thereby increasing the metabolism of nutrients and glucose consumption by the muscles. The increased sensitivity of insulin receptors was helping to reduce blood glucose levels. This effect is like the effect of exercise and physical activity on blood glucose levels. This study aims to determine the effect of cupping therapy on blood glucose levels.